The Effect of Vapocoolant Spray and Baby Shark Vibrator on Children’s Pain during Invasif Procedure - Ely Mawaddah; Mira Utami Ningsih (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2023)
Invasif procedure is a procedure that is often performed on children. This procedure is related to needles that causes pain in children. Children who experienced pain during invasif procedure need treatment to avoid trauma. It is necessary to apply atraumatic care through the use of interventions that eliminate or minimize the psychological and physical distress suffered by children, one of which is the use of vibrators with music and cold compresses to minimize pain. This study aims to determine the effectiveness of giving a baby shark vibrator compare with vapoocoolant spray against pain in children undergoing invasif procedure such as injection and venipuncture. The researcher divided the respondents into 2 groups, the intervention group (baby shark vibrator) and the control group (vapocoolant spray) which are taken randomly with a total of 60 children participating in this study. The assessment of children's pain using the FLACC instrument (face, legs, activity, cry and consolability). The results of statistical tests showed that there was a no significant difference in pain in the intervention group and the control group (p=0.077). The use of a baby shark vibrator can be an alternative to reduce pain in children during invasif procedure because for some children, it is more convenient and distracting.